Cost-Effectiveness of Blood Donation Screening for Trypanosoma cruzi in Mexico. - Gilberto Sánchez-González; Alejandro Figueroa-Lara; Miguel Elizondo-Cano; Leslie Wilson; Barbara Novelo-Garza; Leopoldo Valiente-Banuet; Janine M Ramsey (Public Library of Science (PLoS), 2016)
An estimated 2 million inhabitants are infected with Chagas disease in Mexico, with highest prevalence coinciding with highest demographic density in the southern half of the country. After vector-borne transmission, Trypanosoma cruzi is principally transmitted to humans via blood transfusion. Despite initiation of serological screening of blood donations or donors for T. cruzi since 1990 in most Latin American countries, Mexico only finally included mandatory serological screening nationwide in official Norms in 2012. Most recent regulatory changes and segmented blood services in Mexico may affect compliance of mandatory screening guidelines. The objective of this study was to calculate the incremental cost-effectiveness ratio for total compliance of current guidelines from both Mexican primary healthcare and regular salaried worker health service institutions: the Secretary of Health and the Mexican Institute for Social Security. We developed a bi-modular model to analyze compliance using a decision tree for the most common screening algorithms for each health institution, and a Markov transition model for the natural history of illness and care. The incremental cost effectiveness ratio based on life-years gained is US$ 383 for the Secretary of Health, while the cost for an additional life-year gained is US$ 463 for the Social Security Institute. The results of the present study suggest that due to incomplete compliance of Mexico's national legislation during 2013 and 2014, the MoH has failed to confirm 15,162 T. cruzi infections, has not prevented 2,347 avoidable infections, and has lost 333,483 life-years. Although there is a vast difference in T. cruzi prevalence between Bolivia and Mexico, Bolivia established mandatory blood screening for T.cruzi in 1996 and until 2002 detected and discarded 11,489 T. cruzi -infected blood units and prevented 2,879 potential infections with their transfusion blood screening program. In the first two years of Mexico's mandated program, the two primary institutions failed to prevent due to incomplete compliance more potential infections than those gained from the first five years of Bolivia's program. Full regulatory compliance should be clearly understood as mandatory for the sake of blood security, and its monitoring and analysis in Mexico should be part of the health authority's responsibility.